2017
DOI: 10.1186/s12879-017-2606-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of Pentraxin-3 in patients with sepsis and septic shock in accordance with latest sepsis-3 definitions

Abstract: BackgroundPentraxin-3 (PTX-3) is an acute-phase protein involved in inflammatory and infectious processes. This study assesses its diagnostic and prognostic value in patients with sepsis or septic shock in a medical intensive care unit (ICU).MethodsThe study includes 213 ICU patients with clinical criteria of sepsis and septic shock. 77 donors served as controls. Plasma levels of PTX-3, procalcitonin (PCT) and interleukin-6 were measured on day 1, 3 and 8.ResultsPTX-3 correlated with higher lactate levels as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
53
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 41 publications
5
53
0
1
Order By: Relevance
“…Furthermore, the higher concentrations of PTX3 in non-surviving calves, although not statistically significant, warrant future investigations for its use as a prognostic indicator. The findings of the present study suggest that PTX3 can be an important indicator in calves with sepsis, which is supported by previous studies (Muller et al 2001;Mauri et al 2010;Huttunen et al 2011;Vanska et al 2011;Uusitalo-Seppala et al 2013;Hamed et al 2017) conducted in human medicine.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the higher concentrations of PTX3 in non-surviving calves, although not statistically significant, warrant future investigations for its use as a prognostic indicator. The findings of the present study suggest that PTX3 can be an important indicator in calves with sepsis, which is supported by previous studies (Muller et al 2001;Mauri et al 2010;Huttunen et al 2011;Vanska et al 2011;Uusitalo-Seppala et al 2013;Hamed et al 2017) conducted in human medicine.…”
Section: Discussionsupporting
confidence: 91%
“…Muller et al (2001) also reported that in critically ill human patients, PTX3 concentrations are markedly elevated (SIRS patients; 28 ng/ml, septic shock; 250 ng/ml) compared with control donors (1.04 ng/ml). Hamed et al (2017) determined the diagnostic cut-off values for PTX3 in human patients with sepsis (≥ 5.0 ng/ ml) and septic shock (≥ 9.0 ng/ml). In the present study, PTX3 concentrations in calves with sepsis were also significantly higher (P < 0.01) than in the control group (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that plasma PTX3 levels could be used to evaluate sepsis and septic shock on the first day of sepsis onset. In addition, our study confirmed that circulating PTX3 levels were elevated in sepsis patients and were even higher in septic shock patients, the results of which were similar to previous studies of others . It was also found that PTX3 levels in sepsis and septic shock patients had much more significant correlations with traditional immune parameters than in post‐surgery patients.…”
Section: Discussionmentioning
confidence: 84%
“…The study presented significant and valuable AUCs for discriminating sepsis or septic shock from healthy and post‐surgery controls. Previous studies showed that PTX3 had significant correlations with APACHE II score and SOFA score in sepsis and septic shock patients . Moreover, the plasma PTX3 level could predict 90 mortalities in sepsis patients .…”
Section: Discussionmentioning
confidence: 98%
“…7 Persisting high plasma levels of circulating pentraxin-3 over the first days from onset of sepsis may be associated with mortality as well as with sepsis associated coagulation and fibrinolysis dysfunction. 8 Part from septic situations, studies also indicate that pentraxin-3 is a better marker of infection than C-reactive protein in patients with dengue. 9 Interestingly,pentraxin-3 has also been reported to increase in plasma in patients with acute myocardial infarction.…”
mentioning
confidence: 99%